2021
DOI: 10.1093/pm/pnab142
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of mRNA Expression of IL-6 and mTORC1 and Efficacy and Feasibility of an Integrated Approach Encompassing Cognitive Behavioral Therapy Along with Pregabalin for Management of Neuropathic Pain in Postherpetic Neuralgia: A Pilot Study

Abstract: Objective This study was designed to explore the efficacy and feasibility of cognitive behavioural therapy(CBT) along with pregabalin and compare it with pregabalin monotherapy for the management of neuropathic pain in post-herpetic neuralgia (PHN) patients and to explore the modulation of mRNA expression of interleukin (IL)-6 and mammalian target of rapamycin-1 (mTORC1) genes in these patients. Design Randomized controlled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The pain relief effect is remarkable, a significant downregulation of mRNA expression of IL-6 was observed. 24 Confirming consistent results in East Asian and West Asian populations, however, it is not shown that IL6 level is closely related to PHN prognosis. This study found that serum IL6 levels in patients with PHN in admission are correlated to the Likert scale score on the 14 th day after diagnosis.…”
Section: Discussionmentioning
confidence: 66%
“…The pain relief effect is remarkable, a significant downregulation of mRNA expression of IL-6 was observed. 24 Confirming consistent results in East Asian and West Asian populations, however, it is not shown that IL6 level is closely related to PHN prognosis. This study found that serum IL6 levels in patients with PHN in admission are correlated to the Likert scale score on the 14 th day after diagnosis.…”
Section: Discussionmentioning
confidence: 66%
“…Overall, our study provides information for family‐centered care in patients with NP. First, pain catastrophizing is one of the essential indicators for measuring pain management's effectiveness (Martinez‐Calderon et al, 2019; Saxena et al, 2021; Sisco‐Taylor et al, 2022). In our study, the significant total effect of good family functioning on reducing pain catastrophizing provides some support for family‐centered care.…”
Section: Discussionmentioning
confidence: 99%
“…In group 1, PHN-related NP patients received pregabalin monotherapy alone, while Group 2 patients were treated with a combination of pregabalin together with cognitive behavioral therapy. The results showed that patients in Group 2 had significant downregulation of IL-6 mRNA expression [143].…”
Section: Neuropathic Painmentioning
confidence: 93%